Pengaruh Kepercayaan Konsumen, Brand Image Dan Kepuasan Terhadap Keputusan Pembelian Produk Cosmetic Merek Y.O.U - Efa Nur Diana; Titi Rapini; Siti Chamidah (The Academy Of Management and Business, 2023)
The purpose of this study was to determine the effect of consumer trust, brand image and satisfaction on purchasing decisions for cosmetic products brand Y.O.U. The type of research used in this study is a type of quantitative research with data collection methods used are field research, namely, interviews, observation/observations and questionnaires. In this study, there were 95 consumers who bought Y.O.U Brand Cosmetic Products. Data collection techniques by distributing questionnaires to 95 respondents. Methods of data analysis using validity test, reliability test, multiple linear regression, coefficient of determination, t test and F test. The results of this study indicate that the influence of consumer trust, brand image and satisfaction have a significant effect on purchasing decisions for Y.O.U brand cosmetic products.